2012
DOI: 10.1007/s00217-012-1755-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-microbial metabolites in fonio millet (acha) and sesame seeds in Plateau State, Nigeria

Abstract: We investigated 16 fonio millet and 17 sesame samples by LC/ESI-MS/MS for the spectrum of microbial metabolites contaminating these seeds. Forty-eight fungal and four bacterial metabolites were detected in fonio, while 28 fungal and two bacterial metabolites were found in sesame. Altogether, 55 metabolites were identified in both grains, 18 of which are reported for the first time to naturally occur in cereals and oil seeds. The metabolite concentrations reached 7,280 lg/kg in fonio for aurofusarin and 64,600 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 32 publications
3
33
2
1
Order By: Relevance
“…Both crops are regarded as high energy and oil seeds containing diverse minerals, vitamins and antioxidants (Onyeike and Acheru 2002 ; Borchani et al 2010 ) with additional high protein levels found in melon (Gorskis 1985 ; Bande et al 2012 ). Previous studies have reported the presence of fungal contaminants and/or mycotoxins in melon (Bankole 1993 ; Bankole et al 1999 , 2004 , 2006 ; Fagbohun et al 2011 ; Adeleke et al 2012 ; Fapohunda et al 2014 ; Williams et al 2015 ; Ezekiel et al 2016 ; Nwokocha and Opara 2016 ) and sesame (Mbah and Akueshi 2009 ; Ezekiel et al 2012 , 2014 ; Makun et al 2014 ; Fapohunda et al 2012 , 2018 ; Ogara et al under review ) in Nigeria. However, there is no study comparing the fungal and mycotoxin profiles of these crops sampled across two seasons from any of these top-ranked producing states.…”
Section: Introductionmentioning
confidence: 97%
“…Both crops are regarded as high energy and oil seeds containing diverse minerals, vitamins and antioxidants (Onyeike and Acheru 2002 ; Borchani et al 2010 ) with additional high protein levels found in melon (Gorskis 1985 ; Bande et al 2012 ). Previous studies have reported the presence of fungal contaminants and/or mycotoxins in melon (Bankole 1993 ; Bankole et al 1999 , 2004 , 2006 ; Fagbohun et al 2011 ; Adeleke et al 2012 ; Fapohunda et al 2014 ; Williams et al 2015 ; Ezekiel et al 2016 ; Nwokocha and Opara 2016 ) and sesame (Mbah and Akueshi 2009 ; Ezekiel et al 2012 , 2014 ; Makun et al 2014 ; Fapohunda et al 2012 , 2018 ; Ogara et al under review ) in Nigeria. However, there is no study comparing the fungal and mycotoxin profiles of these crops sampled across two seasons from any of these top-ranked producing states.…”
Section: Introductionmentioning
confidence: 97%
“…The variety of fungal species capable of producing mycotoxins is vast, leading to an even larger diversity of over 300 secondary fungal metabolites already known to possess toxic properties. Studies on mycotoxin contamination profiles in feed and foodstuff reveal that compounds generally do not occur isolated, but in complex mixtures (Domijan et al 2005 ; Ezekiel et al 2012 ; Serrano et al 2013 ; Shephard et al 2013 ; Streit et al 2013 ). In addition, these co-contaminations are not limited to mycotoxins produced by one certain fungal genus.…”
Section: Introductionmentioning
confidence: 99%
“…Il semble moins sensible aux dommages parasitaires pendant le stockage que d'autres céréales (Dansi et al, 2010;Adoukonou-Sagbadja et al, 2007b). Les grains de fonio sont consommés sous diverses formes (couscous, bouillies) et les pailles sont souvent utilisées comme fourrage pour nourrir les bovins, mais aussi les chèvres, les moutons notamment dans les zones les plus arides, où les sources d'alimentation animale sont rares (Cruz, 2004 ;Ezekiel et al, 2012 ;Jideani et Jideani, 2010 ;Jideani, 2012). Pauvre en gluten, le fonio est indiqué pour les personnes diabétiques et ceux qui souffrent du problème de surpoids (Bama, 1999, Vodouhè et al, 2006.…”
Section: Introductionunclassified